Pengaruh Metode Pembelajaran Terhadap Hasil Belajar Keterampilan Lompat Jauh - Sudiadharma Sudiadharma; Abdul Rahman (Seminar Nasional LP2M UNM, 2019)
Abstract. This This experimental study aims to distinguish two learning methods of squat style long jump skills, consisting of command learning methods, and play learning methods. This research was conducted at SMK YPPP Wonomulyo Polewali Mandar Regency, 2018/2019. The experimental method uses two groups pre-test-posttest design. The sample consisted of 30 male students of SMK YPPP Wonomulyo Polewali Mandar Regency divided into two groups, each consisting of 15 male students of SMK YPPP Wonomulyo Polewali Mandar Regency. The data analysis technique is a paired and unpaired ttest analysis technique at the level of trust α = 0.05. The results of this study indicate that (1). There was an increase in the learning outcomes of the long jump skill squat command command learning style. Where the value of t arithmetic = 6.826> t table 2.15 and a significance value of 0.00 <0.05 (2). There is an increase in the learning outcomes of the long jump skill squat playing learning method. Where the value of t count = 4.864> t table 2.15 and the significance value 0.00 <0.05 (3). There is a difference between the command learning method and the play learning method against the squat style long jump learning outcomes. The command learning method is more effective for improving squat style long jump learning outcomes. Where the value of t arithmetic = 11.91 > t table 2.15 and a significance value of 0.00 <0.05Keywords: Influence, Learning Method, Learning Outcomes, Long Jump Skills